An Image-Based 384-Well High-Throughput Screening Method for the Discovery of Biofilm Inhibitors in Vibrio cholerae. - Peach, Kelly C. (Mol Biosyst, 2011)
Bacterial biofilms are assemblages of bacterial cells and extracellular matrix that result in the creation of surface-associated macrocolony formation. Most bacteria are capable of forming biofilms under suitable conditions. Biofilm formation by pathogenic bacteria on medical implant devices has been linked to implant rejection in up to 10% of cases, due to biofilm-related secondary infections. In addition, biofilm formation has been implicated in both bacterial persistence and antibiotic resistance. In this study, a method has been developed for the discovery of small molecule inhibitors of biofilm formation in Vibrio cholerae, through the use of high-throughput epifluorescence microscopy imaging. Adaptation of a strategy for the growth of bacterial biofilms in wellplates, and the subsequent quantification of biofilm coverage within these wells, provides the first example of an image-based 384-well format system for the evaluation of biofilm inhibition in Vibrio cholerae. Application of this method to the high-throughput screening of small molecule libraries has lead to the discovery of 29 biofilm lead structures, many of which eliminate biofilm formation without altering bacterial cell viability.